Innovative development of small businesses in the service sector is the key to increasing the number - Ulmasova Oygul Bakhtiyarovna, (THE INNOVATION ECONOMY, 2026)
This article emphasizes that the rapid growth of the service sector in developed countries is directly linked to the increase in the number of small businesses and their increased revenues (profitability). Examples are provided from the experiences of leading countries.